2022
DOI: 10.1021/acsami.2c20019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Superior DNA Delivery Efficiency of Multicomponent Lipid Nanoparticles: An In Vitro and In Vivo Study

Abstract: Lipid nanoparticles (LNPs) are currently having an increasing impact on nanomedicines as delivery agents, among others, of RNA molecules (e.g., short interfering RNA for the treatment of hereditary diseases or messenger RNA for the development of COVID-19 vaccines). Despite this, the delivery of plasmid DNA (pDNA) by LNPs in preclinical studies is still unsatisfactory, mainly due to the lack of systematic structural and functional studies on DNA-loaded LNPs. To tackle this issue, we developed, characterized, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Endocytosis is a well-studied ED pathway for the transportation of nanoparticles across the cellular membrane, facilitating their internalization into specific cells and subsequent accumulation, which includes phagocytosis, macropinocytosis, clathrin- or caveolin-mediated endocytosis. Conversely, EI internalization mechanisms involve fusion, embedment, and direct translocation ( Quagliarini et al, 2022 ). Traditional small molecular drugs primarily enter cells through passive or active process, whereas nanomedicines enter cells via endocytosis ( Longfa et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Endocytosis is a well-studied ED pathway for the transportation of nanoparticles across the cellular membrane, facilitating their internalization into specific cells and subsequent accumulation, which includes phagocytosis, macropinocytosis, clathrin- or caveolin-mediated endocytosis. Conversely, EI internalization mechanisms involve fusion, embedment, and direct translocation ( Quagliarini et al, 2022 ). Traditional small molecular drugs primarily enter cells through passive or active process, whereas nanomedicines enter cells via endocytosis ( Longfa et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some recent studies demonstrated that DNA-LNPs are constituted by oligolamellar domains whose spatial extension is dependent on the lipid composition. 65 Despite extensive research, a clear correlation between the structure of DNA-LNPs and their lipid composition has yet to be established.…”
Section: ■ Lipid Nanoparticles: Building Upon Lipoplex Milestonesmentioning
confidence: 99%
“…LNP formulation for (p)DNA delivery has been reported in the literature, e.g., for LNP systems as transfection reagents for plasmid DNA (pDNA) [29], for enahnced oral delivery of DNA [30], for increased efficiency of DNA-vectored vaccines/immunoprophylaxis in animals [31], for spherical nucleic acids for intracellular DNA and RNA delivery [32], for transfection of cell model lines [33], as nanocarrier to deliver a cancer vaccine against the benchmark target tyrosine-kinase receptor HER2 in C57BL/6 mice [34], as well as in evaluating studies regarding the role of the influential Microfluidic Formulation of DNA-Loaded Multicomponent Lipid Nanoparticles for Gene Delivery factors [26].…”
Section: State-of-the-art In Lipid Nanoparticle Manufacturingmentioning
confidence: 99%